DIALEKTIKA DOKTRIN DAN HIDUP DALAM TEOLOGI MORAL PERKAWINAN : Sebuah Tinjauan atas Usaha Pembaharuan Teologi Moral Perkawinan Katolik - Moa, Antonius (LOGOS, 2003)
Renewal was a declaration done by the 2nd Vatican Council. It was manifested variously in all its documents, and in specific way the Council summoned the renewal of the moral theology. It means that the Council also required renewal of moral theology of marriage, which was inclining too strict and rigorious in the past. That inclination marked a contradictory between life and doctrin. In the light of renewal doctrin and life are no more seen contradictories but dialectics.